Disentangling consciencism : essays on Kwame Nkrumah's philosophy - Ajei, Martin Odei (African philosophy, critical perspectives and global dialogue., 2017)
This book critically explores the depths of Nkrumah's philosophical thought in order to broaden understanding of it and measures his contributions to contemporary thought in a world in which Africa totters precariously on the peripheries of intellectual influence on human experience.